Clinical and biochemical footprints of inherited metabolic diseases: I. Movement disorders - Ferreira Lopez, Carlos R; Hoffmann, Georg F.; Blau, Nenad (Molecular genetics and metabolism, 2019)
About a third of patients with inherited metabolic diseases with neurologic involvement suffer from a movement disorder, in the form of ataxia, hyperkinetic movements, or hypokinetic-rigid syndrome. We reviewed and updated the list of known metabolic etiologies associated with various types of movement disorders, and found approximately 200 relevant inborn errors of metabolism. This represents the first of a series of articles attempting to create and maintain a comprehensive list of clinical and metabolic differential diagnoses according to system involvement.